ANALISIS EFISIENSI EKONOMI DAN PRODUKSI KEPITING BAKAU (Scylla serrata) DALAM KARAMBA - Ta'aladin, Zamdial (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The objective of this research was to analyisis of economic efficiency, production of Muds Crab that reared in bambbo cage and to determine of density and bamboo cage design that suffable for rearing of Mud Crab(Scylla serrata).Research was used the Factorial Completely Randomized Design with the dffferent treatement consist of density and bamboo cage construction. Size of bamboo cage are 2 x 2 x 0,5 m. The rearing periode of Mud Crabs are 45 days wffh observation and measurement of weight and length growth in each 15 days. For determine of teratement of density and bamboo cage construction on the Mud Crabs production used the statistical test, while the economic analysis was using BlC ratio investement criteria. The P1 ancJ P2 treatement showed the response of high weight growth and signiflCBl1t with Pl The cell system bamboo cage showed the respon of high weight growth and Significant from the boxs system bamboo cage. For the length growth, P1 highly and significant from the others treatement. The BlC ratio analysisi showed that P3 treatement both the cell and boxes system bamboo cage showed the better result, while theP3 BIG ratio value of cell system bamboo cage is highly in compare with the boxes system bamboo cage.